Byproductive labor: A feminist theory of affective labor beyond the productive-reproductive distinction - Whitney, Shiloh (Philosophy and Social Criticism, 2018)
My aim in this paper is to introduce a theory of affective labor as byproductive, a concept I develop through analysis of the phenomenology of various affective labor practices in dialog with feminist scholarship, both on gendered and racialized labor, and on affect and emotion. I motivate my theory in the context of literature on affective and emotional labor in philosophy and the social sciences, engaging the post-Marxist literature on affective and immaterial labor and emphasizing feminist critiques. I argue that affective labor is not only the work of producing affects for others to consume or the reproductive work that rejuvenates and sustains labor power and social life, but also the work of metabolizing waste affects and affective byproducts. Thus, byproductive labor is a neologism I develop to bring into view an affective economy and indeed a political economy of affects to the side of the distinction between productive and reproductive labor in its paid and unpaid variants. I make three central claims: (1) affective labor invariably creates byproducts in the embodied subjectivity of the worker; (2) the unique kind of affective expenditure I call “byproductive” (metabolizing affective surplus, containing affective waste, and producing depleted affective agency) is a defining feature of affective labor not circumscribed by the productive-reproductive distinction; and (3) the marginalized forms of subjectivity and depleted agency constituted through the intersections of this labor with hierarchies of gender, race, and migrant status or global class are themselves byproducts of affective labor. Thus, theorizing affective labor as byproductive captures the uniqueness of affective labor and the forms of exploitation unique to it, but also explains the interaction of affective labor with forms of power that operate through subjection and marginalization. © The Author(s) 2018.
Keywords: amériques; discipline; histoire et politique; philosophie; projet charge mentale; régions géographiques; sciences humaines; thématiques; travail; travail affectif; travail émotionnel; états-unis